2020
DOI: 10.1002/ejp.1541
|View full text |Cite
|
Sign up to set email alerts
|

Novel approach towards musculoskeletal phenotypes

Abstract: Background:The multidimensional array of clinical features and prognostic factors makes it difficult to optimize management within the heterogeneity of patients with common musculoskeletal pain. This study aimed to identify phenotypes across prognostic factors and musculoskeletal complaints. Concurrent and external validity were assessed against an established instrument and a new sample, respectively, and treatment outcome was described. Methods:We conducted a longitudinal observational study of 435 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 36 publications
2
55
0
Order By: Relevance
“…In addition, patients with NP and LBP have several similarities in psychosocial prognostic factors and comorbidities, clinical guidelines for best practice, and lack of specific pathoanatomic causality [11][12][13][14]. While the models for clinical management of musculoskeletal complaints to date have mainly been condition specific, there have recently been calls for management based on characteristics within the biopsychosocial model regardless of pain condition [14][15][16][17]. Studies have also demonstrated that patients with trajectories of NP display similar on most health-related factors as for LBP [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, patients with NP and LBP have several similarities in psychosocial prognostic factors and comorbidities, clinical guidelines for best practice, and lack of specific pathoanatomic causality [11][12][13][14]. While the models for clinical management of musculoskeletal complaints to date have mainly been condition specific, there have recently been calls for management based on characteristics within the biopsychosocial model regardless of pain condition [14][15][16][17]. Studies have also demonstrated that patients with trajectories of NP display similar on most health-related factors as for LBP [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…We recently identified five MSK phenotypes across common non-specific MSK complaints based on generic prognostic factors in MSK pain conditions [12]. The phenotypes were identified by latent class analysis (LCA) and based on 11 prognostic factors covering all aspects of the biopsychosocial domain.…”
Section: Introductionmentioning
confidence: 99%
“…These endeavors have frequently been based on individual characteristics such as symptoms, pain sites, or other prognostic factors, and usually within defined patient groups. Previous studies have found subgroups that differ in severity [55][56][57], or subgroups that are qualitatively distinct, for example in symptoms or personal factors [22,[58][59][60]. For instance, studies using prognostic factors have found subgroups characterized by low risk, mental health issues, physical limitations and pain, and workplace related concerns in patients with musculoskeletal disorders [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Identifying subgroups that can be used to stratify care is challenging and has been a focus of research in some fields for many years [19], mainly in patients with musculoskeletal disorders [20][21][22][23]. Such stratification approaches have shown effective in treatment of patients with low back pain [24].…”
Section: Introductionmentioning
confidence: 99%